The effects of coronavirus disease 2019 pandemic on the South African health system: A call to maintain essential health services - Juliet Nyasulu; Himani Pandya (AOSIS, 2020)
South Africa had its first coronavirus disease 2019 (COVID-19) case on 06 March 2020 in an individual who travelled overseas. Since then, cases have constantly increased and the pandemic has taken a toll on the health system. This requires extra mobilisation of resources to curb the disease and overcome financial loses whilst providing social protection to the poor. Assessing the effects of COVID-19 on South African health system is critical to identify challenges and act timely to strike a balance between managing the emergency and maintaining essential health services. We applied the World Health Organization (WHO) health systems framework to assess the effects of COVID-19 on South African health system, and proposed solutions to address the gaps, with a focus on human immunodeficiency virus (HIV) and expanded programme on immunisation (EPI) programmes. The emergence of COVID-19 pandemic has direct impact on the health system, negatively affecting its functionality, as depletion of resources to curb the emergency is eminent. Diversion of health workforce, suspension of services, reduced health-seeking behaviour, unavailability of supplies, deterioration in data monitoring and funding crunches are some of the noted challenges. In such emergencies, the ability to deliver essential services is dependent on baseline capacity of health system. Our approach advocates for close collaboration between essential services and COVID-19 teams to identify priorities, restructure essential services to accommodate physical distancing, promote task shifting at primary level, optimise the use of mobile/web-based technologies for service delivery/training/monitoring and involve private sector and non-health departments to increase management capacity. Strategic responses thus planned can assist in mitigating the adverse effects of the pandemic whilst preventing morbidity and mortality from preventable diseases in the population.